PENGARUH PERENCANAAN PAJAK, FEE AUDIT, DAN GCG TERHADAP MANAJEMEN LABA DENGAN PEMODERASI KEPEMILIKAN MANAJERIAL - Eko Sudarmanto; Triana Zuhrotun Aulia; Siti Rosmayanty (ICMA Nasional, 2023)
The purpose of this study is to determine the effect of tax planning, audit fees, good corporate governance on earnings management with managerial ownership as moderator for food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) for 2018-2022. This study uses a quantitative approach. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX). The sampling technique use purposive sampling and obtained a sample of 10 companies. The data analysis technique used is moderation regression analysis. The results of this study indicated that audit fees, independent board of commissioners, and institutional ownership have an effect on earnings management, tax planning has no effect on earnings management and managerial ownership is able to moderate audit fees and institutional ownership on profit management, managerial ownership not being able to moderate tax planning and independent board of commissioners against earnings management.